Perancangan Data Warehouse Pada Software Laboratory Center - Chandra, Alvin (Bina Nusantara University, 2010)
The purpose of this study is to analyze the existing database on Software Laboratory Center to obtain necessary information and design data warehouse to integrate existing data to obtain some global information. The methods used are analysis and design method. The method of analysis is done by conducting surveys and analysis of the running system, analysis and identification the weaknesses of the running system, and troubleshooting analysis. And the data warehouse design method is done by applying the nine steps (Nine-Step Methodology) that used by Ralph Kimball's to design star schema. The result is data warehouse that provides some global information which global, relevant, and integrated which can be seen from various points of view that is useful for the leaders to make decisions. Separate data warehouse from operational databases that already exist required by Software Laboratory Center to assist leaders in making strategic decisions in a fast and precise way.